Pronunciation Error on English Diphthongs Made by EFL Students - Desy Riana Pratiwi; Lia Maulia Indrayani (TEKNOSASTIK, 2021)
This research addresses pronunciation errors of English diphthongs made by EFL students. The data were collected from pronunciation recordings of 9 post-graduate students who were studying linguistics in the second year.  Three of the respondents were male and 6 female students. Studies show that different backgrounds and cultures affect sounds and sound styles as they are related to pronunciation or language styles. The purpose of this research was to analyze and describe the pronunciation errors of English diphthongs made by EFL students. Diphthong is divided into two types, namely GA (General American) and SSBE (Standard Southern British English) or commonly referred to as British accent. To collect the data, the researchers recorded students’ pronunciations using a smartphone. The data collected were then analyzed by employing qualitative and quantitative descriptive methods. The results show that 4 students used SSBE diphthong accent and 5 used GA diphthong accents. In this analysis, there were also 4 students who made pronunciation errors in pronouncing [eɪ], [ɛə], [ʊə] and [aɪ] diphthongs, 3 students had problems about [aʊ] and 2 students mispronounced [oʊ] diphthong.